2020
DOI: 10.1128/mbio.01019-19
|View full text |Cite
|
Sign up to set email alerts
|

A Zeaxanthin-Producing Bacterium Isolated from the Algal Phycosphere Protects Coral Endosymbionts from Environmental Stress

Abstract: Reef-building corals form a complex consortium with photosynthetic algae in the family Symbiodiniaceae and bacteria, collectively termed the coral holobiont. These bacteria are hypothesized to be involved in the stress resistance of the coral holobiont, but their functional roles remain largely elusive. Here, we show that cultured Symbiodiniaceae algae isolated from the reef-building coral Galaxea fascicularis are associated with novel bacteria affiliated with the family Flavobacteriaceae. Antibiotic treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 53 publications
6
65
0
Order By: Relevance
“…Moreover, bacteria have been observed inside many types of algae [9][10][11][12][13], indicating the existence of intracellular interactions. Bacteria are known to provide their algal hosts with vitamin B12 [14][15][16][17], increased iron bioavailability [18], carotenoids [19], and growthpromoting hormones [20], though the array of functions is likely much greater.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bacteria have been observed inside many types of algae [9][10][11][12][13], indicating the existence of intracellular interactions. Bacteria are known to provide their algal hosts with vitamin B12 [14][15][16][17], increased iron bioavailability [18], carotenoids [19], and growthpromoting hormones [20], though the array of functions is likely much greater.…”
Section: Introductionmentioning
confidence: 99%
“…This is an essential shortcoming as bacteria also directly interact with Symbiodiniaceae [82,86]. Further corroborating a functional importance of these associations, coral holobionts host conserved algal-bacterial partnerships [83] and bacteria derived carotenoids have been shown to protect the algal endosymbionts (and thereby the holobiont) from environmental stress [87].…”
Section: The Role Of the Bacterial Microbiome In Holobiont Nutrient Cmentioning
confidence: 89%
“…Elsewhere, Thawornwiriyanun et al (2012) recorded 30 °C as an ideal temperature for zeaxanthin production in Sphingomonas natoria. In a recent study, after 192 h of thermal stress at 31.6 °C, Muricauda lutaonensis (a Flavobacteriaceae bacteria) showed zeaxanthin yield of 8.04 × 10 −2 µg/mL when grown in association with a coral Galaxea fascicularis and an alga Symbiodiniaceae (Motone et al 2020). They have suggested that carotenogenesis in M. lutaonensis was governed by oxidative stress and also mentioned that zeaxanthin produced from this bacterium helps the alga and coral holobiont in mitigating environmental stress by reducing the production of reactive oxygen species (ROS).…”
Section: Process Optimisation Of Culture Conditions For Zeaxanthin Yimentioning
confidence: 99%